Health Literacy pada Mahasiswa Kesehatan, Sebuah Indikator Kompetensi Kesehatan yang Penting - Nurjanah Nurjanah; Sri Soenaryati; Enny Rachmani (VISIKES: Jurnal Kesehatan Masyarakat, 2016)
Health literacy Competency is important for health students since they will be a role model for people to do healthy behavior and provide health services to the community. Previous research results in 2014 on students of Faculty of Health Sciences Dian Nuswantoro University showed 31.9% of respondents had low level of health literacy (inadequate and problematic).This research aims to design a program for intervening student health literacy. Data was collected by filling questionnaire, focused group discussion and developing SMS Gateway program. Population was second semester students of Undergraduate Program of Public Health, however the number of students who participated in this study was 82 student from three classes.The results showed low health literacy was experienced by 40.2% of respondents; it was higher than previous study because the number of respondents was bigger. In addition, there were 95.9% of respondents could not answer correctly questions of nutritional fact in NVS measurement. FGD results showed that respondents prefer to use social media and SMS Gateway to receive health messages. Health messages that they need were: reproductive health, nutrition, smoking, drugs, cosmetics, and diet. The recommendation is using social media such as Blackberry Messengers, Line, Instagram, Twitter to broadcast health messages besides SMS Gateway that has been developed.Keywords: health literacy, health student.